2015
DOI: 10.1002/2015jb012152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and pore fluid on the strength of porous limestone

Abstract: The presence of pore fluid in rocks generally reduces brittle strength. The role of water weakening in porous carbonate rocks and the effect of enhanced deformation on concomitant transport property evolution are poorly understood. The interaction between pore fluid and deformation mechanisms in carbonate rocks is complicated by crystal plasticity and solubility in calcite at low temperatures and pressures. To explore this system, we perform conventional triaxial deformation experiments on Indiana Limestone (~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 81 publications
2
22
0
Order By: Relevance
“…Figure shows that the presence of water induced significant weakening in SML (i.e., the onset of C* at a given effective pressure was reduced when the samples were wet). A weakening effect of water on limestone was also reported by Lisabeth and Zhu () and Nicolas et al (). Baud et al () interpreted the measured weakening on SML using the micromechanical model previously used to model stress‐induced grain crushing (Zhang et al, ).…”
Section: Mechanical Datasupporting
confidence: 74%
“…Figure shows that the presence of water induced significant weakening in SML (i.e., the onset of C* at a given effective pressure was reduced when the samples were wet). A weakening effect of water on limestone was also reported by Lisabeth and Zhu () and Nicolas et al (). Baud et al () interpreted the measured weakening on SML using the micromechanical model previously used to model stress‐induced grain crushing (Zhang et al, ).…”
Section: Mechanical Datasupporting
confidence: 74%
“…Most porous rock data are for sandstones, which typically show, under high confinement, a significant reduction of permeability with the onset of shear‐enhanced compaction (Heffer, ; Zhu & Wong, ). Similar investigations of permeability evolution in porous carbonate rocks are limited; nevertheless, the data of Yale and Crawford () for a suite of carbonate rocks (with total porosities ranging from 14% to 42%) and more recent data of Dautriat et al () for Estaillades limestone (porosity 29%), Lisabeth and Zhu () for Indiana limestone (porosity 16%), and Brantut et al () for Purbeck limestone (porosity 14%) show an overall trend of compaction‐induced permeability that is qualitatively similar to the extensive data on sandstones.…”
Section: Introductionmentioning
confidence: 77%
“…The investigation of Dautriat et al () on Estaillades limestone has provided new insights into permeability anisotropy and the dependence on loading paths. Lisabeth and Zhu's () study of Indiana limestone has highlighted the chemical effect of water and temperature on failure and permeability evolution. However, because the range of confining pressure in both studies was somewhat limited, it is difficult to draw broader conclusions on the influence of stress and failure mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since deionized water was used, we expect initially ionic exchange between a limestone sample and the pore fluid, until sufficient calcite has been dissolved and the saturation state of the fluid is in equilibrium with the rock. From experimental observation and model calculation, Lisabeth and Zhu () concluded that the temperature‐dependent dissolution kinetics of calcite is such that pore fluid saturation and equilibrium would require about 50 hr at a temperature of 25 °C. In this study the total duration for saturating and seasoning a sample typically exceeded 3 days, well above the time necessary for equilibrating the fluid‐rock system.…”
Section: The Limestones and Experimental Proceduresmentioning
confidence: 99%